Evaluasi dan Strategi Pengelolaan Sampah Berbasis 3R (Reduce, Reuse, Recycle) di Kecamatan Klungkung, Kabupaten Klungkung - Mertayani, Ni Luh; Sudarma, I Made; Dwipayanti, Ni Made Utami (Bumi Lestari, 2025)
Evaluation and Strategy of 3R-Based Waste Management in Klungkung District, Klungkung Regency can be formulated as the problem, namely how to manage 3R-based waste based on planning, organizing, implementing, and supervising, and how the implementation of waste reduction is successful using the 3R concept and how the 3R strategy in Klungkung Regency in waste management. The purpose of this study is to analyze waste management in terms of planning, organizing, implementing, supervising (POAC). The research process is to use a qualitative research method, namely thematic analysis which is the process of coding information to produce a list of themes, complex theme models or indicators, qualifications that are usually related and by using interview methods with several informants. This research was conducted in Klungkung District, Klungkung Regency, namely by using observation, documentation, and in-depth interviews with several informants, primary data and secondary data as support for the completeness of research data and information. The problems found in this study were analyzed using the POAC (Planning, Organizing, Actuating, Controlling) management theory, in analyzing this research strategy using System Theory. The results of this study include the lack of operational costs for waste transportation, the lack of fuel costs even though they have been funded but the cash flow is still lacking. The conclusion of the study in the implementation of waste management in the transportation process has not been running optimally because there is still a lack of budget provision for purchasing fuel, in the monitoring stage the SOP has not been running well and management has not been maximized and the weakness of more accurate data and information. This study can be useful for the Klungkung Regency Government in the 3R-Based Waste Management Sustainability Program.